Literature Review: Kemampuan Anak Berkebutuhan Khusus Melakukan Kebersihan Diri - Ita Pursitasari; Allenidekania Allenidekania (Jurnal Kesehatan, 2019)
The number of the child with special needed which is quite alarming is one of the health problems that occur in children. The purpose of this writing is to find out the family support in maintaining children with special needs in performing personal hygiene. The child with special needed have health problems or obstacles in various circumstances and classifications, such as lack of interaction in community and school activities, limited activities, emotional and behavioral delays, and limitations of intellectual development. These problems can cause an impact on children's independence, one of which is self-care. In order for the child with special needed to be able do personal hygiene independently, support from the family is needed. The support provided is social support consisting of emotional, instrumental, appreciation and information support.